2020
DOI: 10.1111/dar.13113
|View full text |Cite
|
Sign up to set email alerts
|

Use of a novel prescribing approach for the treatment of opioid use disorder: Buprenorphine/naloxone micro‐dosing – a case series

Abstract: Introduction and AimsBuprenorphine/naloxone is an evidence‐based treatment for opioid use disorder, but an identified limitation is the period of required opioid abstinence prior to induction on the medication. ‘Micro‐dosing’, or using incrementally increasing doses of buprenorphine/naloxone over time, may be a way to overcome this challenge as it can be done in parallel with the ongoing use of other opioids (either illicit or prescribed).Design and MethodsA retrospective case series (January to December 2018)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 11 publications
1
52
0
Order By: Relevance
“…Many patients present to the hospital in the initial stages or ongoing development of opioid withdrawal. ASAM Guidelines recommend a clinical opioid withdrawal score (COWS) of 11 or more before initiating traditional buprenorphine initiation, 9 but some patients cannot tolerate mild or moderate withdrawal and may risk leaving the hospital prematurely 37 . In these instances, we recommend treating acute withdrawal with up to 40 mg of methadone per day and simultaneously beginning a low-dose initiation using a buprenorphine patch.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many patients present to the hospital in the initial stages or ongoing development of opioid withdrawal. ASAM Guidelines recommend a clinical opioid withdrawal score (COWS) of 11 or more before initiating traditional buprenorphine initiation, 9 but some patients cannot tolerate mild or moderate withdrawal and may risk leaving the hospital prematurely 37 . In these instances, we recommend treating acute withdrawal with up to 40 mg of methadone per day and simultaneously beginning a low-dose initiation using a buprenorphine patch.…”
Section: Resultsmentioning
confidence: 99%
“…This may be especially true for patients using fentanyl or other high potency synthetic opioid analogs, 7 which are increasingly prevalent contaminants in the North American drug supply 8 . The standard approach to starting buprenorphine in the hospital can be challenging due to patients’ severe illness, chronic pain, and anxiety around withdrawal 9–12,13 . There is, therefore, an urgent need for strategies to reduce barriers to in-hospital buprenorphine initiation to increase accessibility to this lifesaving medication.…”
mentioning
confidence: 99%
“…Because of its favorable characteristics, microdosing is increasingly being used as a buprenorphine induction strategy 16,18 ; however, a recent systematic review confirmed that published evidence to date is limited to case studies, and no rigorous studies have been conducted. 19 Furthermore, microdosing has not been evaluated in the ED setting despite complexities that could conceivably make this approach favorable for many ED patients (eg, acute intoxication, painful conditions, time pressures, and ED resource limitations that make observed withdrawal difficult).…”
Section: Importancementioning
confidence: 99%
“…The theoretical basis of this approach is that small buprenorphine doses gradually accumulate at opioid receptors, replacing a patient's need for full agonists. Microdosing inductions can and have been used with a range of overlapping opioid agonists (eg, heroin, methadone, hydromorphine, fentanyl) 15–18 . Where patients undertake a microdosing induction concurrently with non‐medical opioid use, physicians or other prescribers counsel them that there is no set expectation to alter illicit drug use but that they may decrease their concurrent opioid use as per their symptoms 15…”
Section: Introductionmentioning
confidence: 99%
“…In response to their own clinical experiences with patients that use fentanyl, some providers have recommended changes to typical practice such as longer opioid abstention periods and more cautious starting doses of BUP/NX [21]. Recent years have seen the development of novel buprenorphine micro-induction regimens that do not require initiation in a state of significant opioid withdrawal and may reduce the risk of precipitated withdrawal [22][23][24]. The median starting doses of these published regimens is 0.5 mg, uptitrated over a median of 6 days; further research is necessary to determine effectiveness and optimal dosing [25].…”
Section: Discussionmentioning
confidence: 99%